Implementation Implications Non-Conviction Based Asset Forfeiture on Notaries Whose Authentic Deeds Are Indicated as Means of Money Laundering - Ni Wayan Gita Pratisthita; Pieter E. Latumeten (Ridwan Institute, 2023)
Money laundering, which arises from illicit activities, typically requires a legitimate document to facilitate the transfer of funds into an asset. Notaries, authorized public officials capable of creating such legitimate documents, may be implicated in money laundering offenses. In the ongoing efforts to combat money laundering, there is an increasing emphasis on asset confiscation without the need for criminal convictions (Non-Conviction Asset Forfeiture), as exemplified in the Draft Law on Asset Confiscation. This study aims to evaluate the concept of Non-Conviction Asset Forfeiture, explore the role of Notaries in preventing money laundering activities, and scrutinize the implications of implementing Non-Conviction Asset Forfeiture on Notaries who authentically notarize documents that may be used for money laundering. The research employs a normative juridical approach focusing on theoretical and statutory considerations. It elucidates the core principles of Non-Conviction Asset Forfeiture, specifically the pursuit of assets derived from criminal activities when the perpetrator cannot be held accountable due to circumstances. Furthermore, the research underscores that Notaries who authenticate documents suspected of facilitating money laundering may face legal consequences, potentially including the confiscation of their assets if they violate relevant laws and regulations.